Pedagogical Opportunities For Improving Methods Of Teaching Writing Skills - Surayyo Juraevna Khamrakhodzhaeva (European International Journal of Pedagogics, 2025)
The article explores the pedagogical potential for enhancing methods of teaching writing skills. Special emphasis is placed on creative writing in a foreign language, highlighting its role in the development of students’ linguistic, cognitive, communicative, and creative abilities. The paper outlines methods and techniques that encourage creative activity, sustain motivation and engagement in the writing process, foster a supportive classroom environment, ensure feedback, and provide assessment of written outcomes. The importance of mastering a foreign language is particularly stressed for economics students preparing to work in an international context.